Avaliação do comportamento gasométrico com fetos transfundidos, em gestantes Aloimunizadas, conforme concentração de Hemoglobina de adulto em sua circulação - Naeme José de Sá Filho (2018)
Introduction: Perinatal hemolytic disease occurs due to the passage, through the placenta, of maternal antibodies to the fetal circulation, leading to hemolysis of fetal erythrocytes and, in extreme cases, death. During the treatment with intrauterine transfusion, little is known about the effect of the concentration of the adult red cells from the blood transfused, in the hemodynamic and the acid-basic equilibrium exchanges of the fetal blood. Objective: To verify if the fetus with progressive elevation of adult hemoglobin concentration after intrauterine transfusion, blood gas values are better compared to anemic fetal carriers of fetal hemoglobin. Patients and methods: From 1998 to 2015, a longitudinal observational study was carried out with 365 transfusions performed on 143 followed fetuses. The concentration of fetal hemoglobin was determined by the Kleihauer-Betke test and the values of pH, BE, SO2, HCO3, pO2 and pCO2 were determined through the umbilical cord venous blood. The cases were separated according to the hemoglobin concentration deficit (delta) compared to the normality curve specified for gestational age. Results: Evaluating the gasometric parameters, being for a deficit less than 5g / dl: pH (p=0,958), pCO2 (p=0,400), pO2 (p=0,493), SatO2 (p=0,698), HCO3 (p=0,495) e BE (p=0,522) and for a deficit greater than 5 g / dl: pH (p=0,601), pCO2 (p=0,065), pO2 (p=0,770), SatO2 (p=0,096), HCO3 (p=0,096) e BE (p=0,525), were not significantly influenced by the gradual replacement of fetal-type red cells by adult-type red cells, regardless of hemoglobin deficiency. Conclusions: Due to the existence of a hematological system with great capacity for metabolic balance, there were no associations between the gasometric parameters and the percentage of replacement of the fetal hemoglobin, that is, regardless of the degree of anemia produced by the hemoglobin deficit.